Alpine skiing. - Kipp, Ronald W., ....- (Champaign : Human Kinetics, 2011)
More than 2,000 ski areas in 57 countries offer fun and excitement to people of all ages-from young children to retirees. Whether you've never stood on skis or you're looking to improve your basic skills, you can depend on Alpine Skiing to help you hit the slopes. In Alpine Skiing, Ronald Kipp introduces novice skiers to the basics of the sport, assists intermediate skiers in refining skills, and advises experts in specialized situations. He prepares you for your adventure with information on conditioning, selecting equipment, and familiarizing yourself with the skiing environment. You'll then find easy-to-follow instruction on skiing fundamentals, such as the wedge turn, the christie and edging skills, parallel turns, and dynamic parallel skiing. You will find additional guidance on the more challenging moguls, powder skiing, tree skiing, and racing slopes. Throughout the book Kipp shares consumer, technique, and safety tips collected from his years of experience as both a skier and an
Instructor. He also provides valuable information on travel and trip planning, including choosing a ski area and accommodations, packing, and flying with your gear. Lists of websites will help you find ski instructors and organizations, shop for equipment and gear, and plan trips around the world. Each chapter also includes Success Check questions that will help you test your skiing knowledge. Alpine Skiing is part of the Outdoor Adventures series, which provides you with the essential information on basic techniques and skills so you can be on your way to an adventure in no time
Inhoudsopgave : Part I. Preparing for the Skiing Adventure Chapter 1. Introduction to Alpine Skiing Chapter 2. Getting Fit for Skiing Chapter 3. Equipment and Gear Chapter 4. Skiing Environment Chapter 5. Learning and Instruction Chapter 6. Trips and Traveling Part II. On the Slopes Chapter 7. Getting Started: The Never-Ever Skier Chapter 8. Wedge Turn Chapter 9. Christie Chapter 10. Parallel Turns Chapter 11. Dynamic
Parallel Skiing
Keywords: Skiën